Existentiell psykoterapi - En introduktion - Serrander, Elisabeth (Socialmedicinsk tidskrift, 2023)
Existential psychotherapy, rooted in existential philosophy and psychology, takes its point of departure in the unique individual’s lifeworld. A basic premise is that our health depends on how we live - if we don’t live well, we don’t feel well. Man’s castability means that we get a basic shape and certain conditions as a result of inheritance and social environment, but that we create ourselves throughout life through our actions. We are thereby co-creators of our personality; we have ability to make choices, prioritize and opt out. Actions define us and we reap their consequences. Existential client work is directed towards exploration, dialogue and understanding. The goal is to increase the clients insight into personal attitudes and life situations. This article provides an introduction to and ways therapists can work with existential therapy.